Utilization of genetic testing among children with developmental disabilities in the United States - Kiely B; Vettam S; Adesman A (The Application of Clinical Genetics, 2016)
Bridget Kiely, Sujit Vettam, Andrew Adesman Division of Developmental and Behavioral Pediatrics, Department of Pediatrics, Steven and Alexandra Cohen Children’s Medical Center of New York, New Hyde Park, NY, USA Purpose: Several professional societies recommend that genetic testing be routinely included in the etiologic workup of children with developmental disabilities. The aim of this study was to determine the rate at which genetic testing is performed in this population, based on data from a nationally representative survey.Methods: Data were analyzed from the Survey of Pathways to Diagnosis and Services, a telephone-based survey of parents and guardians of US school-age children with current or past developmental conditions. This study included 3,371 respondents who indicated that their child had an autism spectrum disorder (ASD), intellectual disability (ID), and/or developmental delay (DD) at the time of survey administration. History of genetic testing was assessed based on report by the parent/s. Children were divided into the following five mutually exclusive condition groups: ASD with ID; ASD with DD, without ID; ASD only, without ID or DD; ID without ASD; and DD only, without ID or ASD. Logistic regression was used to assess the demographic correlates of genetic testing, to compare the rates of genetic testing across groups, and to examine associations between genetic testing and use of other health-care services.Results: Overall, 32% of this sample had a history of genetic testing, including 34% of all children with ASD and 43% of those with ID. After adjusting for demographics, children with ASD + ID were more than seven times as likely as those with ASD only, and more than twice as likely as those who had ID without ASD, to have undergone genetic testing. Prior specialist care (developmental pediatrician or neurologist) and access to all needed providers within the previous year were associated with higher odds of genetic testing.Conclusion: The majority of children in this nationally representative sample did not undergo recommended genetic testing. Research is needed to identify barriers to the use of genetic testing in this population. Keywords: autism spectrum disorders, intellectual disability, developmental delay, genetic screening